The OCI-CV-R: A Revision of the Obsessive-Compulsive Inventory - Child Version. (March 2022) - Abramovitch, Amitai; Abramowitz, Jonathan S.; McKay, Dean; Cham, Heining; Anderson, Kennedy S.; Farrell, Lara; Geller, Daniel A.; Hanna, Gregory L.; Mathieu, Sharna; McGuire, Joseph F.; Rosenberg, David R.; Stewart, S. Evelyn; et al.
Abstract: Background: The Obsessive-Compulsive Inventory-Children's Version (OCI-CV) was developed to assess obsessive-compulsive symptoms in youth. Recent changes in the Diagnostic and Statistical Manual (DSM-5) exclude hoarding from inclusion in the diagnosis of obsessive-compulsive disorder (OCD). Accordingly, the present study examined the reliability, validity, factorial structure, and diagnostic sensitivity of a revised version of the scale – the OCI-CV-R– that excludes items assessing hoarding. Methods: Participant were 1047 youth, including 489 meeting DSM criteria for primary OCD, 298 clinical controls, and 260 nonclinical controls, who completed the OCI-CV and measures of obsessive-compulsive symptom severity, depression, and anxiety at various treatment and research centers. Results: Findings support a five-factor structure (doubting/checking, obsessing, washing, ordering, and neutralizing), with a higher order factor. Factorial invariance was found for older (12–17 years) and younger (7–11 years) children. Internal consistency of the OCI-CV-R was acceptable, and discriminant and convergent validity were adequate and akin to that of its progenitor. Diagnostic sensitivity and specificity were found for a total score of 8 and higher. Conclusion: It is recommended that the OCI-CV-R replace the former version, and that this measure serve as part of a comprehensive clinical assessment of youth with OCD. Recommendations for further research with ethnically and racially diverse samples, as well as the need to establish benchmark scores are discussed. Highlights: The OCI-CV is a common measure of obsessive-compulsive symptom severity in youth. The OCI-CV assesses hoarding, which is no longer considered a symptom of OCD. We used large clinical and control samples to revise the OCI-CV to exclude hoarding. The OCI-CV-R, demonstrates comparable psychometric properties to the OCI-CV. The full OCI-CV-R, as well as norms and a clinical cutoff are provided.